Aplectana hoplobatrachusia sp. nov. (Nematoda: Cosmocercidae) in Hoplobatrachus crassus (Jerdon, 1853) (Anura: Dicroglossidae) from Birbhum District, West Bengal, India - Sou, Sujan Kumar; Sow, Kanchan Kumar; Nandi, Anadi Prasad (Zootaxa, 2018)
Aplectana hoplobatrachusia sp. nov., recovered from the rectum of Jordon’s bullfrog, Hoplobatrachus crassus, (Jerdon, 1853) collected from Lohagram in the Birbhum district of West Bengal, India, is described and illustrated. This species is characterised by absence of a gubernaculum and differs from other species of Aplectana which lack a gubernaculum (viz. A. akhrami, A. artigasi, A. chilensis, A. crossodactyli, A. crucifer, A. delirae, A. dubrajpuri, A. meridionalis, A. papillifera, A. praeputialis, A. tarija and A. vercammeni) by morpho-metrical ranges of males and females and number and distribution of caudal papillae in males which include 4 pairs preanal, 1–2 pairs adanal, 10 pairs postanal and a single median papilla on the upper lip of the cloaca. Aplectana hoplobatrachusia sp. nov. represents the 56th species assigned to the genus and the 4th from India and the 5th from Indian subcontinent.